Perioperative management of severe congenital protein C deficiency. Issue 8 (December 2017) - Watanabe, Kentaro; Kato, Motohiro; Ishimaru, Tetsuya; Hiwatari, Mitsuteru; Suzuki, Tomonori; Minosaki, Yoshihiro; Takita, Junko; Fujishiro, Jun; Oka, Akira
Abstract : N/A: Perioperative care of congenital protein C deficiency has not been well established. Here, we describe a patient with congenital protein C deficiency who underwent laparoscopic fundoplication and gastrostomy at 2 years of age. Preoperatively, we stopped warfarin, administered fresh frozen plasma, and activated protein C. These procedures were performed without bleeding or clotting events, and at 3 days after the procedures, we restarted warfarin. Several episodes of abdominal hemorrhage and purpura fulminans occurred 2–4 weeks postoperatively, and the events were managed conservatively. We conclude that an invasive procedure can be performed in patients with protein C deficiency with appropriate supportive therapy, and postoperative observation for a sufficient length of time is essential to minimize the risk of complications.